Primary cardiac lymphoma (PCL) – diagnostic difficulties - Skalec, Karolina; Litwin, Linda; Drozdz, Katarzyna; Gac, Pawel; Jazwiec, Przemyslaw; Chabowski, Mariusz; Zymlinski, Robert; Molenda, Wlodzimierz; Szuba, Andrzej; Janczak, Dariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Primary cardiac lymphoma (PCL) is the very rare disease that is associated with a high mortality rate. A prompt and proper diagnosis may affect the prognosis, and proper treatment may improve life expectancy. This report documents the case of a 74-year-old female with primary cardiac lymphoma. Unfortunately, the patient died from heart failure on her 23rd day in hospital.